2000
DOI: 10.1093/alcalc/35.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Combination Pharmacotherapy: A Mixture of Small Doses of Naltrexone, Fluoxetine, and a Thyrotropin-Releasing Hormone Analogue Reduces Alcohol Intake in Three Strains of Alcohol-Preferring Rats

Abstract: It is common to treat some diseases with more than one medication simultaneously. Since more than one neurotransmitter system is involved in alcohol-seeking behaviour, then a therapeutic approach that targets more than one system should be more effective in reducing alcohol intake than one addressing a single system. To test this hypothesis, we compared the efficacy of low doses of individual drugs reported to reduce voluntary alcohol drinking to the efficacy of a mixture of these agents at the same low doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Evidence from both laboratory animals and human studies implicates dopamine as one of the major neurotransmitter being involved in drug self-administration and addiction (Piazza et al, 1991, Rezvani et al, 1992, Mason et al, 1997, Di Chiara, 1999, Volkow et al, 1999, Rezvani et al, 2000, Goldstein and Volkow, 2002, Volkow et al, 2002b, Kalivas and Volkow, 2005, Nader and Czoty, 2005. In addition to the mesolimbic dopaminergic system, several other neurotransmitter systems including the serotonergic system have been suggested to be involved in drug self-administration (Rezvani et al, 1990, Rezvani and Grady, 1994, Volkow and Li, 2004, Koob, 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from both laboratory animals and human studies implicates dopamine as one of the major neurotransmitter being involved in drug self-administration and addiction (Piazza et al, 1991, Rezvani et al, 1992, Mason et al, 1997, Di Chiara, 1999, Volkow et al, 1999, Rezvani et al, 2000, Goldstein and Volkow, 2002, Volkow et al, 2002b, Kalivas and Volkow, 2005, Nader and Czoty, 2005. In addition to the mesolimbic dopaminergic system, several other neurotransmitter systems including the serotonergic system have been suggested to be involved in drug self-administration (Rezvani et al, 1990, Rezvani and Grady, 1994, Volkow and Li, 2004, Koob, 2000.…”
Section: Discussionmentioning
confidence: 99%
“…This particular strain of alcohol-drinking rat has been characterized and widely used to study the effects of different compounds on voluntary alcohol consumption (Overstreet et al 1999). Alcohol intake was determined using the standard two-bottle choice method as previously described (Rezvani et al 2007(Rezvani et al , 2000(Rezvani et al , 2009(Rezvani et al , 2010. Briefly, after establishment of a reliable baseline for alcohol and water intake, rats were administered systemically (subcutaneously) in the morning (10:00 am) either with the vehicle (20% (w/v) cyclodextrin), or one of the three doses of JNJ-39220675 (0.3, 3, and 10 mg/kg) or naltrexone (as a positive control, 5 mg/kg, s.c.).…”
Section: Jnjmentioning
confidence: 99%
“…Hence, it is not surprising that preclinical studies are investigating whether combining opioid receptor antagonists with agents that alter activity within the 5-HT and glutamate systems enhances suppression of alcohol intake. It has been found that fluoxetine, a selective serotonin reuptake inhibitor (SSRI) widely prescribed for depression, decreases alcohol drinking in rodents (for a review, see Le et al, 1999) and, when combined with naloxone or naltrexone, is reportedly more effective than either agent alone in reducing alcohol intake (Rezvani et al, 2000;Zink, Rohrbach, & Froehlich, 1999), although increased efficacy is not always seen (Gardell et al, 1997). Preliminary clinical studies combining naltrexone and sertraline (Farren, Catapano, & O'Malley, 1997) and the 5-HT3 antagonist, ondansetron (Johnson, Ait-Daoud, & Prihoda, 2000), have shown promising results for drinkingrelated outcomes and are being followed up with larger randomized clinical trials.…”
Section: Combination Therapymentioning
confidence: 99%